Dextromethorphan improved cyclosporine-induced depression in mice model of despair - Azadeh Mesripour; Mojgan Golbidi; Valiollah Hajhashemi (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: Cyclosporine (Cyc) is a calcineurin inhibitor used in immunosuppressive therapy that may cause psychological problems such as depression. Previous investigations have shown the positive antidepressant effects of dextromethorphan (Dxt). Therefore, the aim of this study was the evaluation of the Dxt effect on Cyc-induced depression in an animal model of despair in two separate cohorts. Experimental approach: Male albino mice were used, first total activity was evaluated by the locomotor test, and then after that, the immobility time during the forced swimming test was measured as an indicator of depression. Cyc, Dxt, and fluoxetine (the reference antidepressant drug) were all administered IP. Tests were performed either 4 h after injection (cohort 4 h) or in separate groups 24 h after injection (cohort 24 h). Findings/Results: Cyc reduced total activity measured after 4 h in the locomotor test and it was normalized after 24 h. Immobility time dose-dependently increased during the forced swimming test and remained so after 24 h (cohort 24 h; Cyc 10, 20, and 40 mg/kg, 157 ± 22, 180 ± 8, and 228 ± 4 s, respectively; Cyc 40 mg/kg P < 0.001 vs control 142 ± 13 s) that indicated Cyc induced depressive-like behavior. Dxt (30 mg/kg) like fluoxetine reduced the immobility time when co-administered with Cyc compared with Cyc and remained effective after 24 h (cohort 24 h; 120 ± 30, P < 0.001 vs Cyc 40 mg/kg alone). Conclusion and implications: Dxt was a useful drug for preventing Cyc-induced depression that remained effective for 24 h in mice. Since interpretation from animal studies to humans must be done with caution further clinical studies on the effect of Dxt in patients suffering from psychological side effects of Cyc may be reasonable.